Patent Landscape Report Hydrogen Fuel Cells in Transportation - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2022)
Durante la próxima década, transformar el sector del transporte para ponerlo en un camino Net Zero requerirá una combinación de innovación tecnológica, toma de decisiones gubernamentales y corporativas, y comportamiento adaptado del cliente. Reducir las emisiones de gases de efecto invernadero por el transporte, un sector responsable de casi el 24 por ciento de las emisiones directas de dióxido de carbono de la quema de combustible, es crucial. Este Informe sobre el panorama de las patentes de la OMPI proporciona observaciones tempranas sobre la actividad de patentamiento junto con información complementaria de noticias en línea, comunicados de prensa e informes financieros corporativos en el campo de las pilas de combustible de hidrógeno en el transporte.
Contents: Acknowledgements... 4; Key findings and insights..... 5; Introduction..... 9; Motivation and methodology of the report.....11; Hydrogen fuel cell technologies for the electrification of transport .....13; General field overview, history, and global patent development of fuel cells..... 13; Hydrogen fuel cell technologies in transport: why hydrogen, and why fuel cells?..... 13; Fuel cell history..... 15; Fuel cell technologies..... 20; General overview.... 20; Polymer electrolyte or proton exchange membrane fuel cells..... 23; Solid oxide fuel cells..... 23; Direct methanol or liquid ammonia fuel cells and reformer technology..... 23; Phosphoric acid fuel cells..... 24; Alkali membrane fuel cells..... 24; Molten carbonate fuel cells.... 24; Patent landscape of fuel cell technologies.... 24; Fuel cell recycling..... 27; Cost analysis fuel cells in transport.... 28; Fuel cell recycling roadmap..... 28; Fuel cell automated production.... 30; Fuel cell technologies in transportation..... 34; Market application breakdown..... 35; Innovation origin view.....37; Patent filings by patent applicant type..... 39; Market view analysis: where are fuel cell patents in transport being filed globally?..... 44; Shifting the analysis from a patent filing count to active patent portfolios..... 47; Dynamic and comparative company analysis..... 48; Top 20 universities and research institutes in the field..... 49; Fuel cell application: personal and commercial road vehicles..... 51; Fuel cells as range extender..... 55; Fuel cell application: shipping and marine vehicles..... 58; Fuel cell application: aviation and above-ground vehicles..... 64; Fuel cell application: rail and track vehicles..... 68; Fuel cell application: special vehicles..... 71; The future of fuel cell technologies in transport..... 77; Technology readiness level (TRL)..... 79; Patent perspective..... 79; Commercial viability.... 80; Customer benefits and problems..... 80; Need for action..... 81; Future drivers..... 81; Economic drivers..... 81; Political drivers..... 82; Roadmap and market outlook for hydrogen technologies in transport..... 82; Annex..... 84; Glossary..... 84; Patent searches..... 87; References.... 94.
Keywords: PATENTES -- GASES DE INVERDNADERO -- TRANSPORTE